Redescription of Pseudhesperosuchus jachaleri (Archosauria: Crocodylomorpha) from the Los Colorados Formation (Norian), Argentina - Leardi, Juan Martín (2025)
Pseudhesperosuchus jachaleri Bonaparte, Citation1969 represents one of the best known early non-crocodyliform crocodylomorphs. The only known specimen, PVL 3830, was described by Bonaparte (Citation1972) in his seminal publication dealing with the Los Colorados Formation (Norian; NW Argentina) faunal assemblage. Afterwards, this taxon was never properly described and depicted, considering that it was figured using drawings in which several parts of the skull and postcranium were reconstructed. In this contribution I redescribe this specimen, recognizing its diagnostic features and identifying features previously unnoticed like the presence of pneumatic features on the quadrate and the base of the braincase (i.e. a large posteroventral recess, basioccipital recess sensu lato). These anatomical traits described here are incorporated in a new data set that corresponds to the fusion of a widely used crocodyliform matrix (Pol et al., Citation2014 and subsequent modifications) and a previous expanded matrix based on basal crocodylomorphs (Leardi et al., Citation2017 with posterior changes). This allowed me to evaluate the phylogenetic position of Pseudhesperosuchus and the phylogeny of non-crocodyliform crocodylomorphs in a more inclusive matrix. The incorporation of most non-crocodyliform crocodylomorphs into the data set will prove useful to test other issues in crocodyliform phylogeny (e.g. the position of Thalattosuchia, monophyly of Protosuchia). Pseudhesperosuchus is recovered at the base of the crocodylomorph clade, in a clade that excludes large-bodied forms (CM 73732, Redondavenator and Carnufex), and in several most parsimonious trees forming a clade with Trialestes romeri from the Ischigualasto Formation of Argentina. Non-crocodyliform crocodylomorphs are found as successive sister taxa to Crocodyliformes, and no internal small clades were recovered (except under extreme conditions of extended implied weighting). As other recent analyses, a monophyletic Solidocrania is recovered, with Dibothrosuchus or Hallopus being the sister taxa it. Unlike previous analyses, Eopneumatosuchus colberti is placed outside Protosuchidae and Crocodyliformes and is the sister taxon of the later clade.